2017
DOI: 10.1002/ijc.30920
|View full text |Cite
|
Sign up to set email alerts
|

Sleep characteristics, light at night and breast cancer risk in a prospective cohort

Abstract: Increasing numbers of women in the US are getting too little sleep. Inadequate sleep has been associated with impaired metabolic function and endocrine disruption. Sister Study cohort participants (n=50,884), completed baseline and follow-up questionnaires on sleep patterns. Incident breast cancers estrogen receptor (ER) status of the tumor were ascertained from questionnaires and medical records. Cox regression was used to estimate adjusted hazard ratios (HRs) and 95% confidence intervals (95% CIs). Analyses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
36
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 53 publications
6
36
5
Order By: Relevance
“…Unlike all three studies (including our study) that assessed outdoor LAN intensity using satellite imagery, two other prospective studies that instead used a questionnaire‐based LAN assessment did not find a significant association. In the Sister Study, women who reported the presence of light or television in the bedroom during sleep did not have significantly elevated risk for overall breast cancer over 7.4 years of follow up (1.09 [0.93, 1.26]) 24 . However, our study did not examine the relationship between LAN and breast cancer risk according to menopausal status.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Unlike all three studies (including our study) that assessed outdoor LAN intensity using satellite imagery, two other prospective studies that instead used a questionnaire‐based LAN assessment did not find a significant association. In the Sister Study, women who reported the presence of light or television in the bedroom during sleep did not have significantly elevated risk for overall breast cancer over 7.4 years of follow up (1.09 [0.93, 1.26]) 24 . However, our study did not examine the relationship between LAN and breast cancer risk according to menopausal status.…”
Section: Discussioncontrasting
confidence: 54%
“…More recently, four prospective studies investigated the associations between LAN and breast cancer risk in large cohorts. Two of these studies found a modest increase in breast cancer risk associated with outdoor LAN levels derived from satellite imagery, 22,23 while the other two studies focused on self‐reported LAN and found no or positive yet nonsignificant associations 24,25 . Findings from one study also suggested that the relationship between LAN and breast cancer may be stronger for ER‐positive (ER+) tumors, 24 supporting a role of the antiestrogen effect of melatonin in breast cancer development.…”
Section: Introductionmentioning
confidence: 98%
“…In other large population-based, predominantly white, prospective cohort studies, similar null results indicating no association between sleep duration and breast cancer were found. [20][21][22][23][24]26,34 However, a report from the Ohsaki Cohort in Japan described a higher risk of breast cancer (HR = 1.62, 95% CI: 1.05-2.50), 19 which differs from our risk estimate of 1.04 (95% CI = 0.94 to 1.14) for Japanese Americans with short sleep duration. The primarily white NIH-AARP Diet and Health Study described a lower risk of breast cancer among short sleepers (HR = 0.84, 95% CI: 0.71-0.98), which differed from our risk estimate of 1.04 (95% CI: 0.92-1.18).…”
Section: Discussioncontrasting
confidence: 99%
“…In other large population‐based, predominantly white, prospective cohort studies, similar null results indicating no association between sleep duration and breast cancer were found . However, a report from the Ohsaki Cohort in Japan described a higher risk of breast cancer (HR = 1.62, 95% CI: 1.05–2.50), which differs from our risk estimate of 1.04 (95% CI = 0.94 to 1.14) for Japanese Americans with short sleep duration.…”
Section: Discussioncontrasting
confidence: 85%
“…Dear Editor, As found by White et al, 1 inadequate or poor quality sleep is associated with an increased risk of breast cancer. In patients, sleep can interfere immune function, alter responses to stress, and impact daytime activities and quality of life which is not only a target in the treatment of patients affected by cancer but also a predictor of response to therapy.…”
mentioning
confidence: 90%